Análise de esforço e impacto na implementação das revisões das normas regulamentadoras 10, 12 e 13 em uma indústria petroquímica - Schumacher, Jacson Barbieri (Universidade do Vale do Rio dos Sinos, 2013)
This work aims to conduct an analysis of the effort of implementing the regulatory rules 10,12 and 13 and the assessment on the revision of these standards and the impact on the management system of a petrochemical plant. Through this work you can see the impact on the business strategy, what actions were necessary for the implementation and progress on results of safety and productivity.
Keywords: Implementação; Impacto; Petroquímica; Implementation; Impact; Petrochemical